Growth Factors Released from Advanced Platelet-Rich Fibrin in the Presence of Calcium-Based Silicate Materials and Their Impact on the Viability and Migration of Stem Cells of Apical Papilla - Cristine Smoczer; Kenneth R. Yuth; Mazin A. Askar; Laura A. Young; Susan B. Paurazas (MDPI AG, 2023)
Advanced platelet-rich fibrin (A-PRF) provides the scaffold and growth factors necessary for stem cells to proliferate and differentiate in successful regenerative endodontic procedures. This study investigates the release of transforming growth factor-β1 (TGF-β1), platelet-derived growth factor (PDGF), and vascular endothelial growth factor (VEGF) from A-PRF in cell culture media in the presence and absence of mineral trioxide aggregate (MTA) or Biodentine. Additionally, this research assesses the viability and migration of stem cells of the apical papilla (SCAP) in previously conditioned media. A-PRF obtained from 14 participants were incubated for 7 days in cell culture media alone or via layering with MTA or Biodentine discs and the release of selected growth factors in the media was evaluated using ELISA. The viability of SCAP grown in conditioned media was measured using the CCK8 assay, while SCAP migration was assessed via a transwell assay by counting migrated cells. The release of TGF-β1, PDGF, and VEGF was significantly higher in media with A-PRF alone than in the presence of either calcium-based silicate material (p < 0.05), which showed no difference from the no-A-PRF control (p < 0.05). None of the tested growth factors released in the A-PRF-conditioned media correlated with clot weight. A-PRF-conditioned media, both with and without calcium-based silicate materials, did not impact SCAP viability and migration (p > 0.05). This study shows that SCAP behavior is not impacted by the decrease in growth factor released in the presence of calcium-based silicate materials and that their role in REPs warrants further investigation.